Unfinished business: America and Cuba after the Cold War, 1989-2001 - McGillion, Chris (Cambridge University, 2013)
The first comprehensive study of U.S. policy toward Cuba in the post-Cold War era, Unfinished Business: America and Cuba After the Cold War, 1989-2001, draws on interviews with Bush and Clinton policymakers, congressional participants in the policy debate, and leaders of the antisanctions business community, and makes an important original contribution to our knowledge of the evolution of American policy during this period." "This study argues that Bush and Clinton operated within the same Cold War framework that shaped the Cuba policy of their predecessors, but also demonstrates that U.S. policy after 1989 was driven principally by the imperatives of domestic politics. The authors show how Bush and Clinton corrupted the policy-making process by subordinating rational decision making in the national interest to narrow political calculations. The result was the pursuit of a policy that had nothing to do with its stated objectives of promoting reforms in Cuba and everything to do with getting rid of Fidel Castro's regime and the institutional structures of the Cuban Revolution.